Adolescent to adult health care transition for persons with intellectual and developmental disability: current barriers, next steps - Ramachandran, Shwetha; Stensland, Solveig; Corder, Julie H.; Cuomo, Carrie; Dao, Thao-Vi; Natowicz, Marvin R. (Frontiers in Pediatrics, 2025)
The transition of health care from adolescence to adulthood is a challenging time, especially for persons with intellectual and developmental disability (IDD), where navigating health care transitions can be particularly difficult. Persons with IDD are an especially vulnerable population and they and their caregivers encounter barriers in obtaining high quality health care transition. These barriers result in the suboptimal utilization of health care transition services and consequent poorer health outcomes. Herein, we discuss barriers to obtaining high quality pediatric to adult transitional health care for persons with IDD. We then discuss next steps, some of them well recognized and others underappreciated, for addressing these barriers and thereby achieving an important public health need: the attainment of high quality pediatric to adult health care transition for persons with IDD.